Leadership and corporate responsibility: a review of the empirical evidence. Issue 1 (8th June 2015) - Mazutis, Daina; Zintel, Christopher
Abstract : Purpose: – The purpose of this paper is to consolidate the state of the empirical research to date on the relationship between leadership and corporate responsibility. Design/methodology/approach: – The authors conduct a comprehensive, systematic and narrative review of all published quantitative studies that have examined the link between leadership and corporate responsibility broadly defined, and the authors put forward an integrative model encapsulating current knowledge in this domain. Findings: – The authors not only identify validated direct, indirect and moderating effects of leadership on corporate responsibility but also point to gaps in the literature that imply important directions for further research. Originality/value: – The authors aim to make the following contributions to both the leadership and the corporate responsibility literatures. First, the systematic and narrative review in and of itself provides an important consolidation of existing knowledge in both domains. Second, the authors confirm that the preponderance of empirical evidence supports that leadership matters to corporate responsibility efforts in organizations. Lastly, the review provides a comprehensive model of the relationship between leadership and corporate responsibility that has important implications for future research and theory building in this field.